The Exploration of the Thermococcus barophilus Lipidome Reveals the Widest Variety of Phosphoglycolipids in Thermococcales - Tourte, Maxime; Coffinet, Sarah; Wörmer, Lars; Lipp, Julius S.; Hinrichs, Kai-Uwe; Oger, Philippe M. (Frontiers in Microbiology, 2022)
One of the most distinctive characteristics of Archaea is their unique lipids. While the general nature of archaeal lipids has been linked to their tolerance to extreme conditions, little is known about the diversity of lipidic structures Archaea are able to synthesize, which hinders the elucidation of the physicochemical properties of their cell membrane. In an effort to widen the known lipid repertoire of the piezophilic and hyperthermophilic model archaeon Thermococcus barophilus, we comprehensively characterized its intact polar lipid (IPL), core lipid (CL), and polar head group compositions using a combination of cutting-edge liquid chromatography and mass spectrometric ionization systems. We tentatively identified 82 different IPLs based on five distinct CLs and 10 polar head group derivatives of phosphatidylhexoses, including compounds reported here for the first time, e.g., di-N-acetylhexosamine phosphatidylhexose-bearing lipids. Despite having extended the knowledge on the lipidome, our results also indicate that the majority of T. barophilus lipids remain inaccessible to current analytical procedures and that improvements in lipid extraction and analysis are still required. This expanded yet incomplete lipidome nonetheless opens new avenues for understanding the physiology, physicochemical properties, and organization of the membrane in this archaeon as well as other Archaea.